A case report of perioperative managements for a patient with gastric cancer and cold agglutinin syndrome. Issue 10 (March 2017) - Xu, Ning; Guo, Shuli; Yu, Jianchun; Ma, Yufen
Abstract: Rationale: Gastric cancer patient with cold agglutinin syndrome (CAS) is an extremely rare entity. This kind of patients is very sensitive to the environment, and they always need scrupulous perioperative treatment, however the experience of perioperative treatment for these patients has been seldom reported. Patient concerns: The patient was a 54-year-old male. He suffered diarrhea for 3 months, and later the gastroscopy found a tumor located in the gastric antrum and the biopsy was performed. The pathological result reported that it was poorly differentiated gastric adenocarcinoma. The patient was previously diagnosed with CAS 8 years ago. Diagnoses: Gastric cancer patient with cold agglutinin syndrome (CAS). Interventions: After 2-month neoadjuvant chemoradiotherapy, the patient underwent open radical distal gastrectomy and D2 lymph node resection. No blood transfusion was performed. Eight days after operation, the patient was discharged. During the perioperative period, scrupulous plan was performed, including careful vital signs monitoring, rigid environment thermal control, infusion warming, proper methods for blood sampling and transmission, and mental relief. Outcomes: Curative resection was achieved and the patient was discharged. The perioperative period was uneventful. Lessons: Because of the fragility of CAS, the perioperative management was vital for this patient. Scrupulous plan may guarantee the safety of the patients.